2007
DOI: 10.5194/acpd-7-14041-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oligomer formation during gas-phase ozonolysis of small alkenes and enol ethers: new evidence for the central role of the Criegee Intermediate as oligomer chain unit

Abstract: Abstract. An important fraction of secondary organic aerosol (SOA) formed by atmospheric oxidation of diverse volatile organic compounds (VOC) has recently been shown to consist of high-molecular weight oligomeric species. In our previous study (Sadezky et al., 2006), we reported the identification and characterization of oligomers as main constituents of SOA from gas-phase ozonolysis of small enol ethers. These oligomers contained repeated chain units of the same chemical composition as the main Criegee Inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
2
12
1
Order By: Relevance
“…These differences were mainly caused by different reaction mechanisms. In the absence of SO 2 , the overall O/C observed in the current study is in agreement with the O/C ratio of oligoperoxides characterized by Sadezky et al 19,20 The slope of zero was attributed to the addition of alcohol or peroxide functional groups to the carbon backbone. This further reinforces previously reported results showing that oligoperoxides formed through the oligomerization pathway of sCI account for the majority of BVE-derived SOA in the absence of SO 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These differences were mainly caused by different reaction mechanisms. In the absence of SO 2 , the overall O/C observed in the current study is in agreement with the O/C ratio of oligoperoxides characterized by Sadezky et al 19,20 The slope of zero was attributed to the addition of alcohol or peroxide functional groups to the carbon backbone. This further reinforces previously reported results showing that oligoperoxides formed through the oligomerization pathway of sCI account for the majority of BVE-derived SOA in the absence of SO 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…This further reinforces previously reported results showing that oligoperoxides formed through the oligomerization pathway of sCI account for the majority of BVE-derived SOA in the absence of SO 2 . 19,20 For the case with SO 2 , the evolution of SOA composition was generally consistent with the classical path that O/C increases when H/C decreases. 47 As the data resulted in a Van Krevelen slope steeper than −2 in Figure 2, this suggests the substantial addition of ketone or aldehyde.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…61 Compared to the barriers of the 4CH 2 OO + HO 2 and 4CH 2 OO + H 2 O 2 reactions, it can be found that the first two CH 2 OO addition reactions in the former case are favored obviously, while the last two CH 2 OO addition reactions in the latter case are preferable. This conclusion is not fully consistent with previous results obtained by Moortgat and co-workers, 24 in which the oligomer formation follows the sequential addition of CIs to RO 2 radicals.…”
Section: Methodscontrasting
confidence: 91%
“…Recently, experimental studies have proposed that oligomers containing SCI as the chain units are the dominant components of SOA. 24,25 However, the formation mechanisms of oligomer ROO(CH 2 OO) n H are not consistent. Sadezky et al 24 proposed that the mechanism contains sequential addition of CH 2 OO to RO 2 radical leading to the ROO(CH 2 OO) n radical adduct, and then the oligomer ROO(CH 2 OO) n H is formed by abstraction of (3)…”
Section: Introductionmentioning
confidence: 99%